In-Place, Seismic and Fatigue Analysis of Offshore Platform for Life Extension - Farisi, Muhammad Al-; Zikra, Muhammad (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2015)
This paper presents reassessment of existing offshore platform in the Ardjuna Field, Northwest of Java, Indonesia. The existing platform of B1C was installed in 1975 and owned by PHE ONWJ. The B1C platform is numerically evaluated for service life extension purposes until the next twenty years. The reassessment analyses focus on in-place analysis, seismic analysis and fatigue analysis. These analyses refer to recommended practice issued by American Petroleum Institute standard. The results indicated that the entire value of unity check for all members fulfill the requirements of API RP 2A - WSD. Analysis of fatigue computation showed that three joints have the fatigue life less than 59 years.